2020
DOI: 10.1155/2020/6239640
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Global Value Chain Embedding on Total-Factor Energy Productivity of Chinese Industrial Sectors

Abstract: In the four decades since China’s reform and opening up, China has been playing an active role in global value chain (GVC) due to its abundant resources. China has gained enormous benefits from opening up, but has also suffered huge energy costs in the process. In this study, we incorporated global value chains and energy consumption into a unified analysis framework and calculated the energy total-factor productivity (ETFP) of China’s industry and the degree of participation in GVC. In addition, in order to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…However, whether GVC promotes the productivity growth or not remains an empirical question that needs empirical answers. The few studies conducted in this area reveal some interesting results which remain inconclusive, while little is known about the case of developing countries such as Africa (Yanikkaya & Altun, 2020;Feng et al, 2020;Liu & Saam, 2021). Our study fills this important gap and provides new evidence for the case of African countries.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…However, whether GVC promotes the productivity growth or not remains an empirical question that needs empirical answers. The few studies conducted in this area reveal some interesting results which remain inconclusive, while little is known about the case of developing countries such as Africa (Yanikkaya & Altun, 2020;Feng et al, 2020;Liu & Saam, 2021). Our study fills this important gap and provides new evidence for the case of African countries.…”
Section: Introductionmentioning
confidence: 67%
“…Both backward and forward participation contribute to the development of an efficient production system in the economies under consideration. Feng et al (2020) utilized the panel smooth transformation model (PSTR) to analyse the data and found that China's energy sector benefits from GVC participation due to an improvement in total factor productivity. Their analysis shows that there is a U-shaped relationship between the two variables.…”
Section: Empirical Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…It depicts that increased TPLI is a sign of industrial upgrading, which ultimately affects the energy intensity of the manufacturing industry (Wang et al, 2020). Moreover, increased participation in GVCs leads to higher technological progress, thus resulting in the growth of total factor energy productivity (Feng et al, 2020). The effect of IS on GTFEP is also positive, but insignificant.…”
Section: Panel Co-integration Testmentioning
confidence: 96%